The role of structural order-disorder for visible intense photoluminescence in the BaZr0.5Ti0.5O3 thin films - Anicete-Santos, M.; Cavalcante, L. S.; Orhan, E.; Paris, E. C.; Simoes, LGP; Joya, M. R.; Rosa, ILV; de Lucena, P. R.; Santos, MRMC; Santos-Junior, L. S.; Pizani, P. S.; Leite, E. R.; et al. (Elsevier B.V., 2005)
The nature of the intense visible room temperature photoluminescence of BaZr0.5Ti0.5O3 non-crystalline thin films is discussed in the light of experimental results and theoretical calculations. The photoluminescence measurements reveal that the emission intensity changes with the degree of disorder in the BaZr0.5Ti0.5O3 lattice. First principles quantum mechanical techniques, based on density functional theory at B3LYP level, have been employed to study the electronic structure of a crystalline model and of structurally disordered models in order to detect the influence of disorder on the electronic structure. An analysis of the electronic charge distribution reveals local polarization in the disordered structures. The relevance of the present theoretical and experimental results on the photoluminescence behavior of BZT is discussed. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: photoluminescence; electronic structure; ab initio calculations